Marketing communications strategies and their role in enhancing the dimensions of the quality of banking service provided - an analytical study of a sample of ethnic commercial banks - Fares Abdullah Kazim; May Hamoudi Abdullah; Thaer Faris Abdullah (Iraqi Journal for Administrative Sciences, 2025)
The study aims to identify the extent of adoption of Banking departments to the variables of marketing communications strategy as well as the extent of their impact in enhancing the quality of service Banking Introduction administration, and to achieve that it questionnaire has been designed and distributed to a sample of the Government Banks and Associations of (12) Bank have been the choice of (50) member to test The relationship between the control strategy and quality Banking services provided variables as well as the impact of that strategy on the quality of service Banking provided, it was reached for many of the conclusions and recommendations, including a correlation relationship with significance between marketing communications strategy variables and the dimensions of the elements enhance the quality of Banking Services Department as well as the presence of impact moral variables independent (advertising, sales promotion, personal selling, direct marketing, public relations) in the approved variables (reliability, trust and credibility, responsiveness, tangibility, empathy), and that advertising is one of the most media impact in the purchasing behavior of customers, but he has not received the attention required as well as the study found a number of recommendations, including the need for the Banking departments develop practical steps interesting key elements of the strategy of marketing communications and activated and create an environment in administrative and marketing to provide services QC occasion along with the introduction of bank employees courses qualifying in the field of marketing communications as well as in customer service to provide the service Banking outstanding and the development of specialized marketing departments of banks surveyed banking.